Musician’s health: Reflective dialogic questions as a pedagogical strategy (Research, Society and Development, 2021)
This paper aimed to develop reflective dialogical questions about risk factors of musical practice as a pedagogical strategy for the prevention of musculoskeletal injuries in music students. This is a literature review, with an exploratory, interpretive and propositional strategy. Additionally, in order to support the discussion, a survey of scientific articles indexed to the Scielo and Google Scholar platforms was carried out. The results were divided into three sections. The first section concerns the possibilities and limitations of educational dialogues in promoting learning. The second section presents a brief contextualization of musculoskeletal injuries related to music education. The third section presents reflective dialogic questions about risk factors of musical practice as a pedagogical strategy for the prevention of musculoskeletal injuries in music students. In the end, it was concluded that reflective dialogic questions can be a way to break communication barriers. They can provide new dynamics in the flow of teaching and learning about the health of the musician and can make it possible to reduce the number of absences from music education due to problems related to musculoskeletal injuries.